Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense Emílio Goeldi, Pará, Belém, Brazil - Monné, Miguel A.; Almeida, Lucia M.; Oliveira, Marcio L.; Viana, Jéssica Herzog; Monné, Marcela L. (Zootaxa, 2017)
The primary types of Cerambycidae (Coleoptera) deposited in the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil (DZUP), Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil (INPA), and in the Museu Paraense Emílio Goeldi, Pará, Belém,Brazil (MPEG) are catalogued. There are 54 primary types of Cerambycidae in the DZUP, 48 in the INPA, and 25 in the MPEG.